2016
DOI: 10.1080/09638288.2016.1193231
|View full text |Cite
|
Sign up to set email alerts
|

Exploring end user adoption and maintenance of a telephone-based physical activity counseling service for individuals with physical disabilities using the Theoretical Domains Framework

Abstract: The findings provide strategies to improve recruitment, adoption, and retention of clients in counseling services and to enhance the experiences of targeted service users. Implications for Rehabiliation Peer support and education for equipment use should be built into physical activity programs to encourage participation among persons with physical disabilities. Programs that encourage physical activity among individuals with disabilities should be designed by practitioners to be responsive to a variety of nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The study allowed us to look at both perceived and observed behaviour change in the nurse intervention delivery and participant responsiveness; this is unlike many other studies, which have tended to focus on only one perspective, which is most often the person delivering the intervention. 176,[178][179][180][181] Nurse comments collected at training, individual session checklists and nurse and participant comments from the qualitative work illustrate the intervention delivery and adaptations in context. The intervention was designed to bring about change at an individual level when delivered in a primary care environment; we have observed that context influences the delivery and implementation of the intervention through adaptation.…”
Section: Comparison With Other Complex Intervention Process Evaluationsmentioning
confidence: 99%
“…The study allowed us to look at both perceived and observed behaviour change in the nurse intervention delivery and participant responsiveness; this is unlike many other studies, which have tended to focus on only one perspective, which is most often the person delivering the intervention. 176,[178][179][180][181] Nurse comments collected at training, individual session checklists and nurse and participant comments from the qualitative work illustrate the intervention delivery and adaptations in context. The intervention was designed to bring about change at an individual level when delivered in a primary care environment; we have observed that context influences the delivery and implementation of the intervention through adaptation.…”
Section: Comparison With Other Complex Intervention Process Evaluationsmentioning
confidence: 99%
“…Approximately, only half of the included studies (n=34) reported the injury characteristics of the participants. The type of SCI was indicated by 2 studies, where participants had both traumatic and nontraumatic injuries [ 20 , 21 ]. Injury levels (ie, cervical, thoracic, and lumbar spine injuries), neurologic completeness, and paralysis (paraplegia and tetraplegia) varied among the participants of the included studies, indicating heterogeneous nature of participants under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 14 articles focused on improving physical activity (PA) and leisure time physical activity (LTPA) participation, motivation, and exercise endurance [ 18 , 20 , 21 , 23 - 25 , 27 ,​ 36 , 43 , 45 - 47 , 49 , 50 ]. There were 11 articles that quantitatively assessed the effectiveness of interventions and services to improve motivation and participation in PA and LTPA ( Multimedia Appendix 4 ) [ 18 , 20 , 21 , 23 - 25 , 27 , 36 , 43 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations